Analysis of Differences in the Assessment of Selected Dimensions of Social Well-being in Terms of Different Levels of Management - Zuzana BIRKNEROVA; Dagmara RATNAYAKE KASCAKOVA (Communications of International Proceedings, 2022)
The aim of this paper is to determine whether there are statistically significant differences in the assessment of selected dimensions of social well-being in terms of different levels of management. The research, which was attended by 110 respondents - business managers, was carried out using the Subjective well-being questionnaire, which was compiled according to Keyes's study (1998) aimed at verifying the theory of well-being. The results of the analysis confirmed the existence of statistically significant differences within the three dimensions of well-being, namely in Social Integration, Social Actualization and Social Contribution. A statistically significant difference between TOP management and first-level management was found in Social Integration, between TOP management and supervisors, and also between first-level management and TOP management in Social Actualization and between TOP management and supervisors in Social Contribution. The findings of the research show that the higher the position a business manager holds in society, the higher the level of social well-being he has, the better he evaluates his quality of life and the less negative emotions he experiences during work.
Keywords: Social well-being; Business manager; Levels of management; Dimensions Introduction